STANDARDIZATION OF PROTOCOL FOR PREPARATION OF RTS BEVERAGE FROM JAMUN JUICE - R. S.GAIKWAD; J. K. DHEMRE; Y. S. DESHMUKH (The Bioscan, 2018)
The investigation on standardization of protocol for preparation of ready to serve beverage from jamun juice was conducted in the Department of Horticulture, Mahatma Phule Krishi Vidyapeeth, Rahuri during the year 2014- 16 to extract and clarify juice from jamun fruits and to standardize the process for preparation of RTS beverage.The juice cum pulp extracted by four different methods showed that maximum recovery was obtained from TM3 (Screw type juice extractor) in jamun Cv. Bahadoli(55.20 %) and Cv. Local (48.40 %).Extracted juice cum pulp was clarified by using four clarification method and TC4 (Pectinase enzyme 2 per cent and incubation at 30 ºC for 4 hours and centrifugation at 10000 rpm for 15 minutes) was found best for recovery of clear juice in jamun Cv. Bahadoli(90.42 %) and Cv. Local ( 89.12 %).Thus, it was found that the treatment T5 (Juice 15%+TSS14ºB +acidity 0.3 % + 50 ppm sodium benzoate)+ garlic 5ml + ginger 5ml (juice extract/lit RTS) recorded the highest sensory score of 8.1 in Konkan Bahadoli and 7.9 in local cultivar in respect of overall acceptability followed by treatment T1 (Juice 15% +TSS14º B + acidity 0.3% + 150 ppm sodium benzoate )which recorded the sensory score of 8.0 and 7.9, respectively.